Constraints in Adoption of Beekeeping as an Enterprise in Nagaland - Singh, A. K.; Singh, Rudra P.; Singh, Namrata (Indian Journal of Extension Education, 2016)
Present study was envisaged and accomplished in order to know the constraints of beekeeping adoption by trained  peasantry. Hundred beekeepers were randomly selected and their opinion was obtained by administering a questionnaire.  The key economic constraints of beekeeping adoption were complications in finance from banks, commencement cost  investment beyond the capacity of trained peasantry and lack of government subsidy in apiculture. The relevance of new  technology, lack of adequate scientific knowledge and inclination towards traditional beekeeping were also constraints of  beekeeping adoption. The socio- psychological constraints unfurled by beekeeping adoption were fear of high risk, fear of  sting in beekeeping and perceived low outcome. All respondents realized honey price is very low but about customer  reliance their doctrine was divisible; majority of respondents broached positively about customer reliance on honey  whereas few faced problem for selling honey.
Keywords: Beekeeping; constraints; adoption; enterprise